Locating Error when Clamping Workpiece between Centers - Slătineanu Laurentiu; Coteaţă Margareta; Dodun Oana; Nagîţ Gheorghe; Hriţuc Adelina; Beşliu-Băncescu Irina; Boca Mihai (MATEC Web of Conferences, 2021)
The total machining error includes some distinct errors summed up by following certain rules. One of these errors is the workpiece locating error, which occurs when the workpiece reference base does not match the workpiece locating surface. The paper analyses different definitions of positioning error, as they were proposed by different researchers or groups of researchers and presents an application valid in the case of turning a cylindrical workpiece with locating between the centers. A definition of locating error that takes into account the total differential of the size of the vector that joins the orientation surface with an element of the fixture was preferred. A fixture version was considered to ensure the locating and clamping of the workpiece on the lathes, with workpiece locating between the centers. This fixture uses a mandrel with a sliding center and an elastic collet.